Outcome of Operative and Non Operative Treatment of Glenoid Fossa Fractures in a Tertiary Care Hospital in Peshawar (Medical Forum Monthly, 2024)
Objective: This study was aimed at reviewing operative and nonoperative treatment of Glenoid fossa fractures in our hospital and view to identifying measures necessary to improve outcome.Study Design: Retrospective studyPlace and Duration of Study: This study was conducted at Orthopedic Department of Lady Reading Hospital, Peshawar from March 2012 to July 2014Materials and Methods: 21 patients of glenoid fossa fractures were included in this series with 14 males and 7 females. Patients with displacement of >5 mm who were fit to undergo surgery within 3 weeks of injury were operated using a posterior Judet's approach. Overall 8 patients with displaced fractures were operated (Group A) while 9 patients with displaced fractures (Group B) and 4 patients with undisplaced fractures (Group C) were managed nonoperatively.Results: The incidence of associated injuries was 57.14%. The mean length of hospital stay was 15.3, 32.5, and 3.9 days in groups A, B, and C, respectively. In group A, average constant score was 86.98. The least constant score was observed for group B (57.97) while group C had an average constant score of 85.9. Brachial plexus injury and fracture-dislocations had poorer outcome.Conclusion: Operative treatment for displaced glenoid fractures is a viable option at centers equipped to handle critically ill patients and subset of patients with fracture-dislocation as opposed to fracture alone should always be treated operatively due to persistent loss of function.